Mononucleotide repeat expansions with non-natural polymerase substrates - Alexander V. Chudinov (Nature Portfolio, 2021)
Abstract Replicative strand slippage is a biological phenomenon, ubiquitous among different organisms. However, slippage events are also relevant to non-natural replication models utilizing synthetic polymerase substrates. Strand slippage may notably affect the outcome of the primer extension reaction with repetitive templates in the presence of non-natural nucleoside triphosphates. In the current paper, we studied the ability of Taq, Vent (exo-), and Deep Vent (exo-) polymerases to produce truncated, full size, or expanded modified strands utilizing non-natural 2′-deoxyuridine nucleotide analogues and different variants of the homopolymer template. Our data suggest that the slippage of the primer strand is dependent on the duplex fluttering, incorporation efficiency for a particular polymerase-dNTP pair, rate of non-templated base addition, and presence of competing nucleotides.